Lifelong Learning, Young Adults and the Challenges of Disadvantage in Europe - Holford, John; Boyadjieva, Pepka; Clancy, Sharon; Hefler, Günter; Studená, Ivana (Palgrave Studies in Adult Education and Lifelong Learning, 2023)
This open access book challenges international policy 'groupthink' about lifelong learning. Adult learning - too long a servant of business competitiveness - should be reimagined as central to democratic society. Young adults, especially from disadvantaged backgrounds, engage more in education and training, and learn more day-to-day at work, if provision is democratically organised and based on enduring and inclusive institutional networks, and when jobs encourage and reward the acquisition of skills. Using innovative qualitative and quantitative methods, the contributors develop a critical perspective on dominant policies, investigating - across the European Union and Australia - how 'vulnerable' young adults experience programmes designed to improve their 'employability', and how 'skills for jobs' policies squeeze out wider - and wiser - ideas of what education and training should do. Chapters show why some provision works for those with poor educational backgrounds, why labour market and educational institutions matter so much, how adult education can empower and expand people's agency, and the challenges of using artificial intelligence in lifelong learning policy-making. Several investigate the pivotal role of workplace learning in organisational life, and in learning during 'emerging adulthood'. Important comparative studies of workplace learning in the metals, retail and adult education sectors show the role of management, trade unions and social movements in young adults' learning.